CENTRALIZED LIFE ACCOUNTING - Tasaddi Kari, Mohammad Javad (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
According to Limperg's dynamic theory, accounting and auditing are rooted in the environment. Due to the continuous change of the environment and its effect on the needs of the audience, accounting is also bound to change and improve in order to maintain legitimacy and meet the needs of its audience. Therefore, accounting is continuously developing. According to the mentioned explanations and the development of urbanization and consequently the appearance of apartments, towers and complexes, the need to design and establish a codified and coherent accounting system for this type of activities is felt. to be Therefore, in this article, we intend to provide a codified framework for accounting apartments, towers and complexes (concentrated life).The use of centralized life accounting (CLA) controls resources and provides a framework for performance evaluation in addition to fulfilling the responsibility of accountability. Also, the development of the accounting field due to the connection between science and its practice will lead to the development of other accounting fields as well.